Parabolic Effect Between Managerial Ownership And Firm Value To Control Agency Conflict - R. Amelinda, Margarita Ekadjaja, Halim.P. Siswanto, K. Nuringsih, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This research attempts to place the ownership structure, which includes managerial ownership, institutional ownership, foreign ownership, and concentration ownership as determinants to predict value of the firm. Managerial ownership will be identified and analyzed on its possibility to form the inverse U-shape relationship pattern, therefore the test on parabolic effect between managerial ownership using Tobin’s Q can be conducted. Meanwhile, such test cannot be conducted to the other three independent variables. This test was applied to non-financial firms whose shares were listed on Indonesia Stock Exchange (IDX) during 2000-2017. The result of panel data regression test concludes that managerial ownership can predict value of the firm, while it is not for institutional ownership and foreign ownership.